Features of the regional tourism product promotion of Mangystau region in the context of the “Experience Economy” development - Bekmurzayeva, Zh.A.; Uruzbayeva, N.A. (BUKETOV BUSINESS REVIEW, 2024)
Object: The main goal of this study is to identify the specifics of promoting the regional tourism product of the Mangystau region in the context of the influence of the “Experience Economy” on it. The hypothesis of this study is that the level of development of infrastructure and, in particular, accommodation facilities is not a determining factor in the influx of incoming tourists (non-residents). Methods: To achieve this goal, the following scientific methods were used: generalization method, structural analysis, quantitative analysis, graphical method. Findings: It is known that the tourist product largely consists of intangible services, the use value and value of which is measured mainly by emotions, new sensations and impressions among tourists. The main source of added value in tourism, according to the concept of the “Economy of Experiences,” today is not just tourist services, but positive impressions and feelings of consumers. In particular, certain dimensions of the experience economy are hypothesized to shape perceptions of well-being. In addition, it is assumed that the perception of well-being can lead to two managerial outcomes: brand identification and intentions to return to it, which will shape the promotion strategy of the tourism product. Conclusions: In the context of growing internal and external competition in the tourism services market, on the one hand, and the increasing spread of the concept of the “Experience Economy”, its influence on the promotion of RTP, it is important to diversify promotion channels in terms of strengthening their emotional component.